2005
DOI: 10.1161/01.str.0000153065.39325.fd
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Disparities in Stroke

Abstract: Background and Purpose-Evidence for ethnic disparities in stroke incidence, severity, and mortality has continued to mount in recent years. However, the picture for disparities in acute management and rehabilitation remains more ambiguous. The objective of this report is to summarize current evidence from stroke epidemiology and studies focusing on disparities in stroke care and disability, suggesting courses for action. Methods-A comprehensive search of current literature on ethnic/racial variation in stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(134 citation statements)
references
References 98 publications
2
127
0
1
Order By: Relevance
“…Several other studies of knowledge of stroke risk factors and warning signs also show consistent racial disparities. 8,9,13,14 Similar to prior reports on knowledge of stroke risk factors and warning signs, we also found that tPA awareness was lower in the oldest age groups who are at the greatest risk of stroke. 7 Limitations of this study include those associated with the Behavioral Risk Factor Survey and other random digit dial surveys.…”
Section: Discussionsupporting
confidence: 88%
“…Several other studies of knowledge of stroke risk factors and warning signs also show consistent racial disparities. 8,9,13,14 Similar to prior reports on knowledge of stroke risk factors and warning signs, we also found that tPA awareness was lower in the oldest age groups who are at the greatest risk of stroke. 7 Limitations of this study include those associated with the Behavioral Risk Factor Survey and other random digit dial surveys.…”
Section: Discussionsupporting
confidence: 88%
“…A greater burden of stroke incidence and mortality for black and Hispanic patients has been established in the literature, though reasons for this disparity are unclear 36, 37, 38, 39. Few studies have looked at presentation to PSCs by race and ethnicity 18, 40.…”
Section: Discussionmentioning
confidence: 99%
“…There may be differences in stroke severity or other rt‐PA inclusion/exclusion criteria across racial groups. Black and Hispanic stroke patients present at younger ages,39, 45 and younger patients tend to suffer milder strokes, by National Institutes of Health Scale 46, 47. This could lead to withholding rt‐PA because of either diagnostic uncertainty or a low perceived likelihood of disability from the presenting symptoms, yet, in 1 multicenter study of young adults with stroke, black patients suffered worse 30‐day mortality and functional outcomes compared to white patients 48.…”
Section: Discussionmentioning
confidence: 99%
“…Mary Cushman ve ark., Afrika kökenli Amerikalılarda beyazlara göre strok riskinin aynı yaş grubu ve cinsiyette % 11.3'e % 9.7 oranında daha yüksek olduğunu belirtmektedirler (22). Irklar arasında; diyabet, sistolik kan basıncı, sol ventrikül hipertrofisi, sigara içme oranında da farklılıklar bildirilmiştir (23,24,25). Kenneth J.…”
Section: Derleme Reviewunclassified